2011
DOI: 10.4103/0970-9290.94684
|View full text |Cite
|
Sign up to set email alerts
|

Report of rare palatal expression of Nevus of Ota with amendment of Tanino′s classification

Abstract: Nevus of Ota, a benign melanocytic pigmentary disorder with rare malignant transformation potential, affects 0.014-0.034% of the Asian and Black population and has a strong predilection for females. It occurs in the area innervated by the first and second division of the trigeminal nerve. Oral manifestation is rarely noted with only 14 cases reported till date. This report documents a case of Nevus of Ota with the infrequently noted oral involvement, in an Indian lady. Since oral manifestation is not acknowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Until now, many studies concerning NO were performed and discussed using Tanino's classificaition289. However, several studies have demonstrated that Tanino's classification leaves a considerable portion of patients unexplained1011. Variants unclassified by conventional classification have been reported and therefore have revealed the weaknesses of the original version of Tanino's classifications.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, many studies concerning NO were performed and discussed using Tanino's classificaition289. However, several studies have demonstrated that Tanino's classification leaves a considerable portion of patients unexplained1011. Variants unclassified by conventional classification have been reported and therefore have revealed the weaknesses of the original version of Tanino's classifications.…”
Section: Introductionmentioning
confidence: 99%
“…8 According to studies, primary orbital melanoma is usually well-circumscribed, this is aligned with findings in our case as demonstrated in the CT Scan. 8,9,10 Malignant melanoma can be accurately diagnosed by ophthalmoscopy, fluorescein angiography, ultrasonography, CT Scan, and MRI. 1,4 Our patient was presented with protrusion and ocular displacement towards superior region of the left eye.…”
Section: Discussionmentioning
confidence: 99%
“…Primary orbital melanoma is usually wellcircumscribed, as demonstrated in the CT Scan. 8,9,10 The management of Nevus of Ota ranges from camouflage, cryotherapy, microsurgery, and laser surgery which is the treatment of choice. 1,2 Orbital exenteration aims to control local tumor and to prevent distant organ metastasis (such as liver, bone, lymph nodes, and brain).…”
Section: Discussionmentioning
confidence: 99%
“…Appearance of palatal pigmentation usually blends with oral mucosa and is typically irregular, ill-defined, and often mottled patch. [10]…”
Section: Discussionmentioning
confidence: 99%